The Terrorism Ahead. - Smith, Paul J., 1965- (Taylor and Francis, 2015)
This book examines the evolving threat of terrorism and draws on the latest research to assess future trends. The author assumes that terrorism will remain a potent threat to the international system throughout the twenty-first century, primarily because of the convergence of two negative trends: the availability of Chemical, Biological, Radiological, and Nuclear Weapons (CBRN) - also known as Weapons of Mass Destruction - and the proliferation of terrorist organizations seeking to achieve mass casualties. Even without the CBRN element, however, Smith maintains that terrorism will remain an on.